2023
DOI: 10.3390/risks11020026
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Risks of Autonomous Vehicles

Abstract: Whilst self-driving cars are not vehicles of the future, but technology that is already available, their acceptance and implementation is heavily limited. People consider them as technology that has a lot of risk—be it technological, IT related, or even ethical. The aim of the present paper is to enrich the existing body of literature of risk perception—and in line with this technology adaption—regarding autonomous vehicles and how they are influenced by demographic and exogenous cultural variables. Whilst the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Past studies have shown that Chinese people's behaviors are largely influenced by people in their interpersonal circle because China is a society with high collectivism culture, so demographic variables are closely related to user preferences [23,25,42,47]. In addition, users' past experience of using ICVs will help form their own attitude toward preferences of innovative HMI features in the subsequent use process [3,22].…”
Section: Demographic Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have shown that Chinese people's behaviors are largely influenced by people in their interpersonal circle because China is a society with high collectivism culture, so demographic variables are closely related to user preferences [23,25,42,47]. In addition, users' past experience of using ICVs will help form their own attitude toward preferences of innovative HMI features in the subsequent use process [3,22].…”
Section: Demographic Informationmentioning
confidence: 99%
“…Although other scholars have introduced new models to measure culture's consequences, they have not been as effective as Hofstede's six dimensions. Some studies have also proved that the influence of basic human factors such as gender and age cannot be ignored while researching culture [23,42].…”
mentioning
confidence: 99%
“…The model has been used in various sectors and for various perspectives; for example, for the prediction of proenvironmental behaviour in hospitality and tourism [44], changing the organisational culture to increase innovation and productivity [45], understanding the perceived risks related to self-driving cars [46], etc.…”
Section: Cultural Factors Influencing Passenger-car-buying Behaviourmentioning
confidence: 99%